The Verbal Configuration In Cell Ads Language (A Critical Discourse Analysis) - Emma Bazergan (Tamaddun Life, 2016)
The study is about the phenomena of The verbal configurationin Cell ads language at describing the forms and meanings behind and the social factor caused. The object of the study is all cell ads in Makassar that have been introduced in media whether visual or non-visual. The study is descriptive in introducing Bourdieu’s social theory towards NourmanFairlough's CDA approach which declares the new prespective from both sides.